An investigation of English student-teachers’ constraints during teaching internship program - Salviana Salviana; Asnawi Muslem; Bukhari Daud (Universitas Syiah Kuala, 2021)
The teaching internship is designed to smooth the transition from teacher to student. At the same time the teaching internship assignment gives the teachers training institutions an opportunity to evaluate the students teaching capabilities. It is one of the most important components of the teacher training program. It is an opportunity for student teachers to put their theoretical studies into practice. The objective of this study is to investigate the constraints faced by student teachers during teaching internship program. The qualitative method was employed in this study. The study involved 26 students who participated in the teaching internship program in 2016/2017 session, Faculty of Teacher Training and Education, University of Syiah Kuala. Covenience sampling technique was used to select the sample. The instruments used to collect data was questionnaire. The data collected was analyzed by using Miles and Huberman’s qualitative data analysis. Based on the questionnaire the result showed that there were fourteen constraints faced by student teachers during teaching internship program. The constraints were mainly in the domains of personal, class participation, class management, instructional, emotional, adjusting to students, and supervision. As teaching practice is an important component of teachers training program, considerable attention must be given to make it more effective and fruitful. Therefore, this study suggests that the cooperation of the faculty and schools in terms of supervision need to be improved in order to optimize the outcome of the program.